Interaction and micellar solubilization of diclofenac with cetyltrimethylammonium bromide: A spectrophotometric study - Hosseinzadeh, Reza; Gheshlagi, Mohammad (Collection of Czechoslovak Chemical Communications, 2009)
In this study, the interaction of diclofenac (Dic) with cationic surfactant cetyltrimethylammonium bromide (CTAB) was investigated. The effect of cationic micelles on solubilization of diclofenac in aqueous micellar solution was studied at pH 6.8, 29 °C and various drug concentrations. The binding of diclofenac to CTAB micelles was accompanied by a batochromic shift in the drug absorption spectra. The solubility of diclofenac increased with increasing surfactant concentration as a consequence of the association between the drug and micelles. From the results, the binding constants Kb, was obtained. By using the pseudo-phase model, the partition coefficient between the bulk water and CTAB micelles, Kx, and the Gibbs energy of binding were calculated. The value of binding constant and partition coefficient are increased by increasing of diclofenac concentration.
Keywords: lékové interakce; kvantitativní vztahy mezi strukturou a aktivitou; diklofenak; Diclofenac; Financing, Organized; financování organizované; povrchově aktivní látky; Drug Interactions; vazebná místa; Quantitative Structure-Activity Relationship; Binding Sites; Surface-Active Agents